2013
DOI: 10.1371/journal.pone.0071757
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Activity Is Altered in a Ground Based Murine Model of Microgravity and Proton Radiation Exposure

Abstract: Immune system adaptation during spaceflight is a concern in space medicine. Decreased circulating leukocytes observed during and after space flight infer suppressed immune responses and susceptibility to infection. The microgravity aspect of the space environment has been simulated on Earth to study adverse biological effects in astronauts. In this report, the hindlimb unloading (HU) model was employed to investigate the combined effects of solar particle event-like proton radiation and simulated microgravity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…In addition, results from these studies indicated that T cell activation was decreased in the irradiated mice (1 or 2 Gy) with or without simulated hypogravity (PWS). Similar results were observed in experiments using mice exposed to SPE-like proton radiation with and without simulated hypogravity produced by HS (134, 138). In these experiments, mice were suspended prior to and after SPE proton radiation exposure and total leukocyte numbers and splenic lymphocyte functions were evaluated on days 4 or 21 after the radiation exposure with and without HS.…”
Section: Acute Radiation Effectssupporting
confidence: 85%
See 3 more Smart Citations
“…In addition, results from these studies indicated that T cell activation was decreased in the irradiated mice (1 or 2 Gy) with or without simulated hypogravity (PWS). Similar results were observed in experiments using mice exposed to SPE-like proton radiation with and without simulated hypogravity produced by HS (134, 138). In these experiments, mice were suspended prior to and after SPE proton radiation exposure and total leukocyte numbers and splenic lymphocyte functions were evaluated on days 4 or 21 after the radiation exposure with and without HS.…”
Section: Acute Radiation Effectssupporting
confidence: 85%
“…The changes in peripheral leukocytes in animals post-irradiation have been evaluated in ICR mice irradiated with 225-kVp X-rays (132), γ-rays from 60 Co (133) or 137 Cs (134–136), protons with energies of 50-MeV (133), 51-MeV (137), 70-MeV (133), 74-MeV (134, 135), 78.4 MeV (138) and 1-GeV protons (137, 139) as well as protons with eight different energies between 31 and 75 MeV and simulated SPE protons with energies between 30 and 150 MeV (140). The changes in peripheral leukocytes have also been examined in ferrets irradiated with 60 Co or 137 Cs γ-rays and 110-MeV protons (141, 142) and Yucatan minipigs irradiated with 6-MeV electrons (130), 6+12-MeV electrons and SPE protons (143, 144).…”
Section: Acute Radiation Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…(v) T-cell activation was reduced in mice exposed to SPE-like radiation with or without simulated hypogravity (either partial weight suspension or hindlimb suspension) (e.g. [4]). (vi) Radiation and simulated hypogravity had synergistic effects on immune system biological endpoints (e.g.…”
mentioning
confidence: 99%